Thermal performance evaluation and energy saving potential of semi-transparent CdTe in Façade BIPV. (15th January 2022) - Alrashidi, Hameed; Issa, Walid; Sellami, Nazmi; Sundaram, Senthilarasu; Mallick, Tapas
Highlights: Semi-transparent thermal assessment revealed that least transparency CdTe PV glazing can have U-values as low as 1.52 W/m 2 K. The use of least transparency PV glazing can reduce 96% of solar heat gains and 23.2% of cooling energy compared to conventional clear glazing. South-west building orientation achieved better energy saving over all sampled transparency. Abstract: Semi-transparent PV glazing are promising in Building Integrated Photovoltaic (BIPV) applications. They provide daylight control, energy saving and power generation. The selection of optimal Photovoltaic (PV) glazing requires the accounting for various factors such as location, orientation and glazing transparency. In this work, thermal performance of Cadmium telluride (CdTe) based semi-transparent PV glazing of different transparencies was evaluated in UK for South and South-West orientations. Thermal performance was analysed in terms of U-value, SHGC and cooling load. Results revealed that least transparency CdTe PV glazing can have U-values as low as 1.52 W/m 2 K. The use of least transparency PV glazing can reduce 96% of solar heat gains and 23.2% of cooling energy compared to conventional clear glazing when used in South-West orientation. The selection of optimum glazing was discussed taking into consideration occupants' optical comfort and health.